Technology Alliances and Firm Performance: Portuguese SMEs in an EU-Sponsored Research Setting - Carvalho, Adão (2010)
This thesis is concerned with the relationship between R&D (research and development) alliances and firm performance. It investigates whether SMEs (small and medium-sized enterprises) have performance improvements through participation in government sponsored R&D alliances and attempts to understand the extent to which they are capable of turning alliance outcomes into performance. The thesis analyses simultaneously the alliance performance and firm performance and looks at the influence of the initial conditions and implementation process on both. Complementary to this, the study addresses the issue of organisational learning from alliances. The empirical evidence is based on the experience of a sample of Portuguese manufacturing SMEs from several traditional sectors who participated in the collaborative programme CRAFT (1994-98) sponsored by the EU (European Union). The data were collected through face-to-face interviews, using a structured questionnaire for guiding them. The study aims primarily at capturing the firm’s perspective, with the CRAFT programme regarded as a source of resources the firm uses in pursuit of its objectives. The successful cases, though quite few, illustrate the potential performance benefits SMEs can achieve with the CRAFT model of partnering, if the projects are technically successful and provided the conditions to exploit the alliance outcomes can also be met. Alliance success however does not necessarily imply better firm performance. In general, the real impact on the firms’ performance indicators fell below the initial expectations and more than 60% of all firms in the study did not have a significant impact on performance. Nevertheless, that does not necessarily mean alliance failure or dissatisfaction with the alliance performance. Turning alliance outcomes into firm performance is not an automatic process and the thesis identifies several internal and external factors which may impede the successful exploitation of alliance outcomes. The thesis also distinguishes several barriers to learning which had an influence on the ability of firms to learn from alliances.